Influence of addition of calcium oxide on physicochemical properties of Portland cement with zirconium or niobium oxide - Tanomaru-Filho, Mario [UNESP]; Garcia, André Cresto [UNESP]; Bosso-Martelo, Roberta [UNESP]; Berbert, Fabio Luis Camargo [UNESP]; Reis, José Maurício dos Santos Nunes [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Wolters Kluwer, 2015)
Context: Calcium oxide (CaO) may be added to mineral trioxide aggregate (MTA) or Portland cement (PC) to improve physicochemical and biological properties. Aims: To evaluate the physicochemical properties of PC associated with radiopacifiers and CaO. Materials and Methods: MTA Angelus, PC + 30% zirconium oxide (Zr), or 30% niobium oxide (Nb) associated with 10 or 20% of CaO were evaluated. Gilmore needles were used to evaluate initial and final setting time. Compressive strength was evaluated after the periods of 24 hours and 21 days. pH was analyzed after 3, 12, 24 hours, 7, 14, 21 days. Solubility and flow tests were performed based on the ISO 6876. The data obtained were submitted to analysis of variance and Tukey tests (P ≤ 0.05). Results: The associations with 10% CaO showed greater strength that the associations with 20% CaO. The shortest initial setting time was observed for the association PC + Zr + 20% CaO and MTA. All the cements presented alkaline pH. The flow of all cements was similar. The highest solubility was found in the associations with 20% CaO. Conclusion: The addition of CaO to PC favored the alkaline property and the PC + Zr + 20% CaO presented setting time similar to MTA.
Keywords: Calcium oxide; endodontics; mineral trioxide aggregate; physicochemical properties; portland cement